The Effectiveness of Mini Primer STR CODIS in DNA Degradation as the Effect of High-Temperature Exposure - Ahmad Yudianto; Fery Setiawan (Analytical Cellular Pathology)
Background. More and more today, forensic identification through deoxyribonucleic acid (DNA) examination has achieved greater recognition in supporting Indonesia’s law enforcement. Such examination is to determine the origin of a child, paternity cases, genealogical relation, or identifying unknown crime victims. However, along with the development of this DNA material examination, problems arise. DNA undergoes a degradation, commonly known as degraded DNA, which is one of the serious issues frequently encountered by forensic and DNA experts. Some forensic DNA experts take one of the alternatives to overcome this issue by implementing a mini primer set that is through a method to reduce the size of STR assays on DNA core locus examination. Methods. In this study, the writers conduct research using the mini primers of CSF1PO, FGA, and D21S11 of the molar teeth exposed to 500°C temperature for 20 and 30 minutes and 750°C for the same amount of time.Result. The findings show the DNA contents of molar teeth significantly (p<0.05) decreased as the effect of high-temperature exposure. PCR result visualization shows CSF1PO is the only locus detected with mini primer exposed to 750°C temperature for 30 minutes (the highest exposure during this research). Conclusions. This finding suggests that this locus is potential in examining identification through DNA analysis, especially on a degraded condition as the effect of high-temperature exposure. Besides, this could accelerate the identification process especially on mass disaster events or criminal cases.